Archival metadata practices and challenges in managing digital manuscripts - As'ad, Muhammad; Indrawardani, Ken Fitria; Cahyaningrum, Gita Amalia; Kamajati, Dhatu (Record and Library Journal, 2025)
Background of the study: Metadata plays a critical role in ensuring the accessibility, interoperability, and long-term preservation of digital manuscripts within archival collections. However, inconsistent practices across institutions present significant challenges for standardization and archival sustainability. Purpose: This study aims to identify key challenges in manuscript metadata management within archival contexts and to analyze differences in practices across selected national and international repositories. Method: A qualitative descriptive approach was employed through literature review and document analysis of approximately 50 metadata records. Data were collected from five repositories—Khastara (National Library of Indonesia), BRIN Digital Repository, the British Library, Europeana, and UNESCO Memory of the World—and analyzed thematically to identify recurring patterns and gaps. Findings: Repositories highlight different metadata priorities: Khastara emphasizes descriptive details, BRIN focuses on administrative and technical identifiers, the British Library provides strong provenance and historical context, Europeana prioritizes rights and interoperability, and UNESCO underscores heritage significance and preservation. These variations illustrate the archival challenges of achieving consistent metadata standards. Conclusion: The study highlights the importance of cross-institutional alignment in strengthening sustainable archival metadata practices. Theoretically, it situates metadata as both a technical and cultural construct; practically, it offers insights for archival institutions to improve strategies. Future research should expand repository coverage and involve user perspectives on archival access and use.